Characteristics of Milk Production Systems in rural settlements in the city of Euclides da Cunha Paulista/SP, region of Pontal do Paranapanema (Research, Society and Development, 2022)
The objective was to characterize the Milk Production Systems (SPLs) of the rural settlements of Euclides da Cunha Paulista/SP. Semi-structured forms were applied in loco in 100 SPLs, in order to collect data on socioeconomic, technical and productive aspects and the use of ecological practices. It was observed a low level of education, a high average age, low labor force, and low adherence to producer groups - associative forms. However, it was found that the analyzed producers have good experience and strong ties with dairy farming. The SPLs studied are small milk producers, 97% with an average total production of up to 200 L/day-1, with little infrastructure and low technological level. The use of agrochemicals is moderate, probably due to the low production intensification. The feeding of the herd is characterized by extensive grazing, with the use of supplementary feeding in periods of scarcity, and high dependence on external food. The use of shade in pastures is common, but inefficient. Allopathic medications are used in 100% of the SPLs, with low adherence to alternative products. The management of waste was considered poor. In general, the results confirm the diversity among the studied SPLs, with low levels adopted in technological tools and in the application of ecological-based practices. Actions that strengthen the activity are necessary, as well as the encouragement to adopt more sustainable practices.